Potential Analysis of Rubber Smallholding Development in Mandailing Natal Regency, North Sumatera Province - Hadijah Siregar; Santun R.P. Sitorus; Atang Sutandi (Forum Pasca Sarjana, 2012)
Development of preminent commodity of rubber is one of Mandailing Natal Regency  Government’s strategy to improve society prosperity. To support the mentioned things, this research was conducted with purpose of determining location  suitability for the development of  rubber plantation  based on land evaluation, analysing of financial and marketing feasibilities of rubber smallholding, and analysing the directive of rubber smallholding potential development in Mandailing Natal  Regency by using mapping and descriptive analysis. The  research result shows that acreage of potential area for the development of rubber plantation  in Mandailing Natal Regency is 460 849 ha (70.41%). Financially, the enterprise of rubber  smallholding in every land suitability class is feasible. The market chain of rubber in Mandailing Natal Regency  is not efficient enough. The location which is able to be recommended for the development of rubber plantation in Mandailing Natal Regency based on potential location, financially and relevant government regulations is 201 875 ha (30.84%). The performance of rubber smallholding  plantation in Mandailing Natal Regency  is influenced by agricultural extension service officer, the availability  of farmer group, rubber productivity and availability of agricultural infrastructure. Nowdays, rubber processing factory should be built in Mandailing Natal, considering that raw materials are widely available and added value will contribute for regional development.